Herbal antivirals : natural remedies for emerging & resistant viral infections - Buhner, Stephen Harrod (Storey Publishing, 2021)
"In this comprehensive guide, the author profiles the plants that have proven most effective in fighting viral infections and provides in-depth instructions for preparing and using formulations to address the most common infections and strengthen immunity, safely and naturally. The updated 2nd edition also includes an expanded guide to COVID-19"--